Three‐phase transformerless photovoltaic inverter without common mode leakage current. Issue 9 (17th January 2022) - Yao, Zhilei; He, Xiangyu; Gan, Jiwei; Mao, Saijun
Abstract: Since three‐phase transformerless (TPT) PV inverters have large common mode leakage current (CMLC), a TPT PV inverter without CMLC is proposed. The proposed inverter is derived from three single‐phase half‐bridge inverters and a boost converter. Grounds of the PV array and three‐phase loads are connected directly, so no CMLC exists in the TPT solar inverter. Operating principle, stability analysis, and loss calculation and example of the proposed three‐phase inverter are illustrated in detail. The pulse‐width modulation (PWM) and sinusoidal PWM control methods are used in the boost converter and three‐phase inverter, respectively. The proposed inverter is a stable system. Finally, simulation and experimental results of a 900‐W TPT PV inverter confirm the theoretical analysis. The CMLC in the proposed inverter is only about 0.8 mA, which is mainly caused by the ground line inductance and oscilloscope probe noise. Abstract : (1) A three‐phase transformerless (TPT) PV inverter without common mode leakage current (CMLC) has been proposed, which consists of a boost converter and a three‐phase inverter. (2) Grounds of PV array and three‐phase loads are connected directly, so there is no CMLC in the proposed three‐phase inverter. (3) Operating principle of the proposed three‐phase inverter is illustrated. In addition, experimental results confirm the theoretical analysis.